Think Piece: Christian and African Perspectives on Stewardship of Creation - Lehlohonolo J. Mathibe (Environmental Association of Southern Africa, 2011)
Genesis 1: 24 & 25 read thus: Then God said, let the earth bring forth living creatures after their kind: cattle and creeping things and beasts of the earth after their kind; and it was so. God made the beasts of the earth after their kind, and the cattle after their kind, and everything that creeps on the ground after its kind; and God saw that it was good. According to Christianity and African religious systems and cultures, God created everything: heaven and earth, and all living and innate creatures. As the aforementioned verses from the bible say, 'God saw that it was good'. Thereafter, God created human beings to be the chief stewards of the entire creation. Then: ... the LORD God took the human being and put him/her into the Garden of Eden to cultivate it and keep it. (Genesis 2: 15) So, the two main issues that will be in my mind as I explore the Christian principles as well as the African perspectives on the stewardship of creation are: • The entire beautiful (or good) creation belongs to God; • Human beings are the stewards of creation - their duty is to 'cultivate and to keep it'. Christians and Environmental Justice Christians have often been blamed for the neglect of the environment. For example, according to Lynn White Jr: Christianity, in absolute contrast to ancient paganism and Asia's religions (except, perhaps, Zoroastrianism), not only established dualism of man and nature but also insisted that it is God's will that man exploit nature for his proper ends ... By destroying pagan animism, Christianity made it possible to exploit nature in a mood of indifference to the feelings of natural objects ... Hence we shall continue to have a worsening ecological crisis until we reject the Christian axiom that nature has no reason for existence save to serve man. (White, 1967) White's (1967) criticism is based on interpretation of Genesis 1: 28, where God is by and large understood as saying that human beings are the only important species on earth, so they must have 'dominion' or should exploit everything else on earth. Indeed many critiques, such as White (1967) are not entirely false. For example, the Umthatha Mission Congress of the Methodist Church of Southern Africa (MCSA) in 2004 did not do justice to the issues pertaining to the environment. As a result, the MCSA's 'fifth' pillar of mission (Environmental Justice) was an afterthought - and many people in the MCSA still know and preach only about four mission pillars (imperatives). Generally, very few preachers say anything (preach) on the importance of the environment to Christians. However, there are many Christian (and non-Christian) men and women who have dedicated their lives to ensure that the earth we have inherited is passed on to the next generations as beautiful to the eyes of God as it was when he created it many, many years ago. Certainly, all of us have a role to play - no matter how small.